2015
DOI: 10.1111/crj.12381
|View full text |Cite
|
Sign up to set email alerts
|

Spirometric prediction equations and the relationship between metabolic syndrome and spirometric parameters from an island in Fujian, China

Abstract: MS is a risk factor for decreased lung function in island residents ≥30 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The ndings in our analysis are counter to studies looking at adult lung response to hypertension, which may be due to the age difference in the populations. A study conducted among 2,607 participants older than 30 years old residing in Fujian, China identi ed metabolic syndrome (OR: 4.623, 95% CI: 3.626, 5.894), which includes high blood pressure, as a risk factor for decreased lung function [29]. In a population-based study among 1,319 adults aged 40 to 65 years old, high blood pressure was associated with lowered FEV1 (P = 0.04) and FVC (P = 0.01) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings in our analysis are counter to studies looking at adult lung response to hypertension, which may be due to the age difference in the populations. A study conducted among 2,607 participants older than 30 years old residing in Fujian, China identi ed metabolic syndrome (OR: 4.623, 95% CI: 3.626, 5.894), which includes high blood pressure, as a risk factor for decreased lung function [29]. In a population-based study among 1,319 adults aged 40 to 65 years old, high blood pressure was associated with lowered FEV1 (P = 0.04) and FVC (P = 0.01) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing decreased FVC in patients with MS ( 32 34 ) and an association between decreased FVC (L) and MS in a patient group ( 33 ). In a study recruiting 4001 adults, decreased FVC (L, %) was shown to be associated with each metabolic risk factor (waist circumference, systolic blood pressure, and serum triglyceride level) and MS ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing decreased FVC in patients with MS (32)(33)(34) and an association between decreased FVC (L) and MS in a patient group (33). In a study recruiting 4001 adults, decreased FVC (L, %) was shown to be associated with each metabolic risk factor (waist circumference, systolic blood pressure, and serum triglyceride level) and MS (35).…”
Section: Discussionmentioning
confidence: 99%